L2 Vocabulary Acquisition through Narratives in an EFL Public Elementary School - Maria Nelly Gutierrez Arvizu (IAFOR Journal of Education, 2020)
Teaching English as a Foreign Language (EFL) has exponentially grown in the past decades as it has become part of the curricula from kindergarten to higher education. In many countries, governments have conducted initiatives that resulted in the implementation of English classes in public education settings. The use of narratives in language teaching has been regarded as an effective way to teach vocabulary as stories provide a natural context for language input. However, there is a need to assess the effectiveness of narrative instruction. This study investigated the effect of using stories and pre-teaching vocabulary in a public elementary school in northwestern Mexico. A total of 167 students from third to sixth grade participated. A narrative intervention was conducted in the experimental and comparison groups. The experimental groups were pre-taught vocabulary in the stories through visuals and stories in the participants’ native language (L1), Spanish. A vocabulary assessment was administered three times (pretest, posttest, and delayed posttest) to determine if there were statistically significant differences within and between groups. The tests scores were analyzed using Friedman and Mann Whitney U statistical tests. The results showed that narratives overall helped in developing vocabulary for EFL young learners. Furthermore, the experimental group obtained slightly higher scores at the delayed posttest showing that pre-teaching vocabulary and using the L1 may contribute to increasing vocabulary knowledge in the second language (L2). In EFL public education contexts, using effective teaching strategies promotes acquisition and retention that ultimately lead to communicative competence in the L2.